Analysis and Review of Tin Oxide-Based Chemoresistive Gas Sensor. Issue 3 (3rd May 2016) - Velmathi, G.; Mohan, S.; Henry, Rabinder
ABSTRACT: Different type of mechanisms of gas sensing, various factors that affect the mechanisms, ways to improve the gas sensitivity, state of the art of fabrication techniques and materials used are reviewed. The work also discusses a novel type of gas sensor derived based on the reviewed mechanisms and materials. The development of semiconductor-based gas sensors using tin oxide which is simple to implement, low cost and offering good stability and sensitivity is discussed.